RANCANG BANGUN KELISTRIKAN SISTEM PENYIRAMAN OTOMATIS SELADA BERBASIS ARDUINO UNO - Verawati, Laura; Nuhgraha, Yoddy Agung (Jurnal Mahasiswa Terapan; Vol 1 No 1 (2024): Jurnal Mahasiswa Terapan, 2024)
Farmers usually water when the weather is very hot which results in drought, therefore plant owners water manually by providing water according to a schedule. As an effort to overcome the problem of watering curly lettuce plants, a final project research was created with the title "Electrical Design of an Arduino Uno-Based Automatic Lettuce Watering System." Literature study is the stage where the author looks for information about the tools that will be researched by collecting data from similar works. previously. Based on testing of an Arduino Uno-based automatic watering tool, using an automatic and manual system where the automatic system in this tool is taken based on a predetermined time using RTC (Real Time Clock) DS1307. Based on the electrical design carried out, this tool was designed using Fritzing software and requires an AC current of 2.968 A. because the AC pump uses 0.568 A, the indicator light uses 0.02 A, the power supply uses 2A, the dimmer uses 0.09 A, RTC (Real Time Clock) using 0.18 A, Arduino Uno 0.25 A. In testing the circuit, we achieved 100% success because when testing the device no errors occurred and did not result in component damage.